Government Actions And The Mineral Industry (The National Institute for Occupational Safety and Health (NIOSH), 1980)
Duty on Lead Reduced. -On December 28, the President signed H.R. 5047 which reduces the duty on unwrought lead from 3.5% ad valorem to 3% ad valorem, with a floor level of 1.0625 cents per pound, effective retroactively from January 1, 1980, through June 30, 1983. Pacific Northwest Power Bill Passed. -On December 5, the President signed S. 885 which will enable the Bonneville Power Administration to guarantee 20-year contracts to its 15 major industrial customers in exchange for higher rates. In effect, the bill will have industrial customers pay some of the costs of building additional generating facilities in the Northwest, of which thermal units are expected to be a major part. BPA supplies power to six primary aluminum producers which operate eleven plants having over 30% of the primary aluminum capacity in the United States.